Towards uncertainty-aware and label-efficient machine learning of human expressive behaviour - Tellamekala, Mani Kumar (2022)
The ability to recognise emotional expressions from non-verbal behaviour plays a key role in human-human interaction. Endowing machines with the same ability is critical to enriching human-computer interaction. Despite receiving widespread attention so far, human-level automatic recognition of affective expressions is still an elusive task for machines. Towards improving the current state of machine learning methods applied to affect recognition, this thesis identifies two challenges: label ambiguity and label scarcity.